(untitled) (Research, Society and Development, 2022)
Law nº. 13.288/16 regulates vertical integration contracts, indicating the obligations and responsibilities required in contractual relationships between integrated producers and integrators. The general objective of the research is to carry out a multidisciplinary approach on the relationship of integration between rural producers and agribusiness. It also seeks to analyze in a general way the behavior of the agro-industrial productive sectors, as well as the social, economic and environmental effects generated by the insertion of this contractual modality in the national legal system. The research was based on theoretical investigation and through bibliographic review analyzing scientific publications in national journals, gathering, comparing and identifying through a technical-legal approach, through the systemic method, the behavior of agro-industrial productive sectors. The searches for academic works were carried out through informational resources, in electronic databases (SCOPUS and WEB OF SCIENCES), digital libraries (CAPES and SciELO Thesis Database) and through the academic search engine (Google Academic). works were not restricted by vernacular, but limited by date of publication (2015 to 2022). Data collection followed two pillars: exploratory and selective reading and recording of extracted information. The result of the study showed, among other aspects, that the Vertical Integration Contract regulated by Law nº. 13.288/16, when effectively applied to agro-industrial systems, improves operational/productive efficiency and strengthens the competitive positioning of the agro-industrial sector, mainly due to the legal certainty that integrated producers and integrators have come to have in commercial relations.